The Role of the Islamic Guidance Center as an Information and Integration Site for Mualafs in Selected Zones of Peninsular Malaysia - Awang, Azarudin; Che Mat, Azman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The widespread establishment of Islamic Guidance Centres in Malaysia highlights the importance placed on providing guidance and support to new converts. Apart from describing the development of da’wah in Malaysia and its stages, Muslim converts are also able to channel information about the truth of Islam to the original community and rectify the misconception of being Muslim to the original Muslim community. Thus, this study aims to examine the role of the Islamic guidance center as a center of information about Islam for mualafs (Muslim converts). as well as to identify its role as an Islamic resource for converts in terms of inter-racial integration. This study used a qualitative method, by interviewing five individuals who are directly involved in the management of Muslim converts in Malaysia. The study results found that the Islamic guidance center, whether managed by the Religious Department or NGOs, functions as an Islamic information center by providing basic information about Islam such as Islamic beliefs, Syariah and morals. In another aspect, this guidance center also serves as a source of integration to re-establish intra-ethnic relations with different beliefs and inter-ethnic relations. This research investigates the effectiveness of services designed to assist Muslim converts in integrating with the Muslim community. It explores both the strengths and weaknesses of these services to identify areas for improvement. On the other hand, it provides additional information to the missionary organizations either at the government or NGO level to further strengthen its role in disseminating information about Islam and catalyzing national integration.